Bacillus Calmette–Guerin vaccination and multiple sclerosis: A population‐based birth cohort study in Quebec, Canada. (10th March 2022) - Corsenac, Philippe; Parent, Marie‐Élise; Wolfson, Christina; Arbour, Nathalie; Duquette, Pierre; Benedetti, Andrea; Richard, Hugues; Stäger, Simona; Rousseau, Marie‐Claude
Abstract: Background and purpose: The bacillus Calmette–Guerin (BCG) vaccine could reduce the incidence of multiple sclerosis (MS) through immunomodulation. Previous studies, presenting some limitations, reported no association. We re‐examined this association in a large cohort focusing on relapsing–remitting MS (RRMS). Methods: The cohort included 400, 563 individuals, and was linked with the Quebec provincial BCG vaccination registry and administrative health data. Individuals were followed up from 1983 to 2014 and then within Period 1 (1983–1996) and Period 2 (1997–2014), for the occurrence of MS. Incident MS cases were defined as those with ≥3 hospital or physician claims for MS. Subjects with ≥1 drug reimbursement for MS disease‐modifying therapies were classified as RRMS. Cox proportional hazards regression was used to estimate hazard ratios (HRs) over the follow‐ups, adjusting for potential confounders. Possible effect modification due to sex was assessed. Results: A total of 178, 335 (46%) individuals were BCG vaccinated. There were 274 (0.06%) incident MS cases identified in 1983–1996, and 1433 (0.4%) in 1997–2014. No association was found with RRMS, either in Period 1 (adjusted HR [HRadj ] = 0.96, 95% confidence interval [CI] = 0.63–1.45; 96 cases) or in Period 2 (HRadj  = 1.02, 95% CI = 0.85–1.23; 480 cases). The remaining MS cases, for whom the phenotype was unknown, were positively associated with BCG over the entire follow‐up (HRadj  = 1.25, 95% CI = 1.10–1.41; 1131 cases) and in Period 2 (HRadj  = 1.33, 95% CI = 1.17–1.52; 953 cases). No interaction with sex was found. Conclusions: Findings suggest that BCG vaccination does not decrease the risk of RRMS, and that future studies should consider phenotypes of MS. Abstract : Bacillus Calmette–Guerin (BCG) vaccination was not associated with incidence of relapsing–remitting multiple sclerosis (MS) over the entire follow‐up (1983–2014). For the remaining MS cases, of unknown phenotype and likely including all forms of MS, an association with BCG vaccination was observed only in the second period of follow‐up (1997–2014).